2001
DOI: 10.1074/jbc.m009004200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-induced Change of the Oligomerization State of αB-crystallin

Abstract: alphaB-crystallin in cells can be phosphorylated at three serine residues in response to stress or during mitosis (Ito, H., Okamoto, K., Nakayama, H., Isobe, T., and Kato, K. (1997) J. Biol. Chem. 272, 29934-29941 and Kato, K., Ito, H., Kamei, K., Inaguma, Y., Iwamoto, I., and Saga, S. (1998) J. Biol. Chem. 273, 28346-28354). In the present study, we determined effects of phosphorylation of alphaB-crystallin on its oligomerization state, mainly by using site-directed mutagenesis, in which all three phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
2
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(153 citation statements)
references
References 39 publications
10
135
2
6
Order By: Relevance
“…[135]). Similar discrepancies exist in the literature with regards to the effect of phosphorylation on Bc's chaperone activity [133,134,148,150]. Various factors may account for these apparent differences including the target protein used to assess the chaperone activity, the final concentration of sHsp in the assays (wild-type Hsp27 dissociates at low concentrations and therefore may be predominately dimeric, like the phosphorylated form, in some assays [136,138]), and buffer and temperature conditions of the assay, all of which have been shown to influence sHsp chaperone activity [133].…”
Section: Phosphorylationsupporting
confidence: 71%
See 1 more Smart Citation
“…[135]). Similar discrepancies exist in the literature with regards to the effect of phosphorylation on Bc's chaperone activity [133,134,148,150]. Various factors may account for these apparent differences including the target protein used to assess the chaperone activity, the final concentration of sHsp in the assays (wild-type Hsp27 dissociates at low concentrations and therefore may be predominately dimeric, like the phosphorylated form, in some assays [136,138]), and buffer and temperature conditions of the assay, all of which have been shown to influence sHsp chaperone activity [133].…”
Section: Phosphorylationsupporting
confidence: 71%
“…The main advantage of phosphomimicking forms is that they afford a single homogeneous isoform of the protein. Significantly, phosphomimics of Bc and Hsp27 have similar attributes to the phosphorylated forms of the protein with regards to their oligomeric distribution, chaperone activity, subcellular localisation and cellular trafficking [136,143,150,151]. For example, the translocation of αBc to the nucleus and its association with nuclear speckles during mitosis is phosphorylation-dependent and this is replicated by the S19D/S45D/S59D αBc phosphomimic [143] and both in vitro phosphorylated Hsp27 and the S15D/S78D/S82D 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Hsp27 phosphomimic have comparable abilities to prevent the aggregation of target proteins in vitro [136].…”
Section: Phosphorylationmentioning
confidence: 99%
“…We expected this might be due to the phosphorylation of the protein. This could be supported by a previous study in which the phsphorylation of aB-crystallin was enhanced in U373MG cells after heat shock [36]. An association of aB-crystallin with the vimentin filaments in NIH 3T3 cells was also found after a 43°C heat shock challenge [37].…”
Section: Gfap Is Able To Coassemble With Nestin and Vimentinsupporting
confidence: 80%
“…This method has been employed previously for αB-crystallin and led to similar effects as endogenously phosphorylated αB-crystallin with regards to its oligomeric distribution [122], subcellular localization [123] and cellular trafficking [124]. Biophysical characterisation studies of these phosphomimics have shown that an increase in the number of sites that are phosphorylated decreases the oligomerization of the protein [122] by disrupting the dimeric substructure within the oligomer [125]. Studies using these phosphomimics against both amorphous and fibrilforming target proteins have shown that the effect of phosphorylation of αB-crystallin on its chaperone activity is target protein specific [95].…”
Section: The Effect Of Post-translational Modifications On the Chapermentioning
confidence: 99%